PENGARUH LATIHAN FISIK (SENAM JANTUNG SEHAT) TERHADAP KADAR TNF- α DAN KADAR GULA DARAH PADA PENDERITA OBESITAS - Yulia Fitri; Nunung Sri Mulyani; Ramlan Silaban; Zulfahri Zulfahri (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract Obesity is one of unresolved health problem in Indonesia. Based on the data of Indonesian health profile in 2011, the prevalence of nutritional status of adult population (>18years) in Aceh of overweight was 10,9% and obesity 13,14%. Obesity is a risk factor for development of varous deseases such as diabetes mellitus, hypertension ad heart disease, this occurs because of the role molecules that exist in adipose tissue Tumor necrosis factor alpha (TNF-α) is cytokine that tended to increase in patients with obesity and blood sugar levels. Physical exercise (gymnastic healty heart) is one of activity that can effect of TNF-α levels and blood sugar level in people with obesity. This study is aimed at understanding the impact of physical exercise (gymnastic healty heart) on lowering TNF-α levels and fasting blood sugar of obesity.The research design is quasy experimental with observational pre-post test design. The obese people aged 18-21 years was 25 samples. The sample are given physical exercise (gymnastic healty heart) for 4 weeks.. The data is analyzed by using univariate and bivariate and tested by using T-test dependent and correlation person. Based on the result of this study, it was found that physical exercise did not significant on TNF-α (p=0,11), but physical exercise is significant on fasting blood sugar level (p=0,03). There was no correlation between TNF-α level and fasting blood sugar level before and after Physical exercise is done ( p=0,059 and p=0,192).Keywords : Physical exercise, TNF-α level, fasting blood sugar level and obesity